Strandpromenaden längs Ume älv : ett gestaltningsförslag med fickparken som hjälp - Unosson, Victor (SLU/Dept. of Landscape Architecture, Planning and Management (from 130101), 2025)
This thesis explores and reflects on the potential of ‘pocket parks’ as a concept and idea to support a design process within the field of landscape architecture. The design proposal is situated in the city of Umeå in northern Sweden, in collaboration with the local municipality, and focuses on a section of the waterfront promenade between the areas of Öbacka strand and Strömpilen. Emphasis is placed on the promenade’s unique characteristics, such as its wide and far-reaching views, its dry-meadow qualities, and the municipality’s desire for water access. Additional themes - such as context and connections, green infrastructure, noise, topography, cultural history, landslide risk and erosion, bathing culture and safe swimming - are also addressed. Jadwiga Krupinska’s method presented in the book ‘What an Architecture Student Should Know’, specifically ‘Analysis through Synthesis’, is applied as a meta-process to address the research questions. However, it is interpreted and simplified to fit the scope of the thesis and to make the somewhat nebulous design process more comprehensible for the reader. Based on the findings, it can be concluded that pocket parks can serve as a supportive tool in the design process, as they offer niches relevant for creating site-specific spatial qualities within small areas - a highly relevant aspect for narrow waterfront promenades - and play an important role in urban planning overall.